Buffalo nation : the children are crying - Abbey, Leslye; Snowflake Video Productions; Soundview Media Partners ([Bellmore, N.Y.] : Snowflake Video Productions, 2014)
The Lakota Sioux and many other indigenous Nations are forced to live on the "Reservation," a designated prisoner of war camp. The film is a saga of displacement, neglect, deprivation, abolishment of traditional beliefs, language, mores and culture. Yet, despite the many challenges, the Lakota will not give up.
David Swallow, Jr., Dakota High Hawk, Fr. Lyle Noisy Hawk, Alfred Swallow.
Videographers, Leslye Abbey, Alfred Leftwich, Keith Norman ; photographers, Lesley Abbey, Alfred Leftwich, Q. Sakamaki ; editors, Jeffrey Miller, David Salazar, Dan Belluci ; Lakota narration, Milo Yellow Hair ; .
In English; English subtitles for non-English dialogs.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed May 5, 2017).
Keywords: Lakota Indians -- Social conditions; Pine Ridge Indian Reservation (S.D.) -- Social life and customs; Nonfiction films; Documentary films; Feature films; Internet videos; Streaming video